2015
DOI: 10.1371/journal.pone.0134820
|View full text |Cite
|
Sign up to set email alerts
|

Is the OJIP Test a Reliable Indicator of Winter Hardiness and Freezing Tolerance of Common Wheat and Triticale under Variable Winter Environments?

Abstract: OJIP analysis, which explores changes in photosystem II (PSII) photochemical performance, has been used as a measure of plant susceptibility to stress. However, in the case of freezing tolerance and winter hardiness, which are highly environmentally variable, the use of this method can give ambiguous results depending on the species as well as the sampling year and time. To clarify this issue, we performed chlorophyll fluorescence measurements over three subsequent winters (2010/11, 2011/12 and 2012/13) on 220… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 38 publications
(75 reference statements)
1
38
2
Order By: Relevance
“…Interestingly, tall fescue Festuca arundinacea leaves show a great decrease at all steps of OJIP and F300 parameters in response to high-temperature stress, but pre-acclimation treatment inhibit such declines (Hu et al, 2015). Intriguingly, Rapacz et al (2015) suggest that DI 0 /CS 0 values increase with increasing levels of PSII damage, which is the opposite to what we found (Fig. 2M).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, tall fescue Festuca arundinacea leaves show a great decrease at all steps of OJIP and F300 parameters in response to high-temperature stress, but pre-acclimation treatment inhibit such declines (Hu et al, 2015). Intriguingly, Rapacz et al (2015) suggest that DI 0 /CS 0 values increase with increasing levels of PSII damage, which is the opposite to what we found (Fig. 2M).…”
Section: Discussioncontrasting
confidence: 99%
“…through the increased of energy flux dissipation per reaction center (DI 0 /RC), leading to dysfunction of PSII. Rapacz et al (2015) showed that DI 0 /RC parameter increase with increasing levels of PSII damage in wheat under low temperature. The I and P fluorescence intensities on the OJIP induction curve and the F300 parameter also decrease in wheat plants exposed to Pb stress (Kalaji and Loboda, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results obtained in our work are consistent with other studies because fluorescence measurements have already been used to determine any differences in the frost tolerance of winter wheat (also in field testing). The results obtained by Rapacz, Sasal, Kalaji, and Ko scielniak (2015) showed that the OJIP test (fast fluorescence kinetic measurements) is a reliable indicator of the winter hardiness and freezing tolerance of common winter wheat and Triticale under unstable winter environments (field testing).…”
Section: Discussionmentioning
confidence: 99%
“…The studies include e.g., high light stress (Oukarroum and Strasser 2004), nitrogen deficiency (Cetner et al 2017, Samborska et al 2018, salinity (Dąbrowski et al 2016), water deficit, drought stress (Kiani et al 2008, Czyczyło-Mysza et al 2011, Wang et al 2012, Jedmowski et al 2014, Rapacz et al 2019, action of herbicides (Lazár et al 1997a(Lazár et al , 1998, and waterlogging (Bertholdsson et al 2015). The studies focused on temperature effects on OJIP shape and derived parameters have addressed both low (e.g., Fracheboud et al 1999, Rapacz et al 2015, Husičková et al 2019 and high (Pastenes andHorton 1996, Azam et al 2015) temperature.…”
Section: Introductionmentioning
confidence: 99%